A análise do discurso nas relações de poder e os possíveis impasses para a implantação do Sistema Integrado de Gestão: um estudo de caso na Universidade Federal da Paraíba - Domiciano, Dâmaris Queila Paredes Oliveira (2019)
This study aimed to evaluate the delay in the implementation of the SIG at the Federal University of Paraíba and investigated the impact of this system on power relations, through an analysis of the discursive strategies used by the UFPB employees who held managerial positions in the postgraduate and postgraduate programs as well as the teachers who worked as a manager during the implementation of the SIG, analyzed in the perspective of the administrative technicians, in the position of secretaries and of the professors who held positions of leadership, in the period of 2009-2018, analyzing mainly the relationship between managerial versus subordinate, from the application of a semistructured interview, in a given Center of the UFPB, resulting in the application of six interviews with technical-administrative servers and seven interviews with teachers who have or still hold the position of head.As a theoretical contribution, in order to base this research, we focus mainly on the studies of Marcuschi (2014), Foucault (2014), Bakhtin (2012), Orlandi (2008), Pêcheux (1997) and Bourdieu (2001) to discuss the discourse in power relations; Regarding the Integrated Management System, we will mainly use the considerations of Laudon & Laudon (2010), Corrêa and Gianesi (1994) and Guarino (2015). This research is an applied research, we follow the teaching of Gil (2008) and Minayo (2009). We use the teachings of Lakatos and Marconi (2014) on exploratory and descriptive nature, with a qualitative approach. The main results obtained were that, both the technical-administrative servers and the professors with managerial positions, pointed out as impasses for the effective implementation of the system the lack of training and the lack of communication between the sectors. Contrary to the expectations of the UFPB, according to the results obtained, after the implementation of the GIS, the administrative technical servers, essentially, had accumulation of activities and slowness in the processes, the chiefs-teachers continued to demand that both manual and digital work continued, there being duplicity in the work of the servers and provoking in these servers physical and emotional wear and tear. In conclusion, the fundamental objective of the UFPB with the implementation of the GIS was to provoke the democratization of the activities, however, due to the failures in its implementation there was an emphasis on the hierarchization of labor relations, since, who was in a superior hierarchical position, was exempted to carry out their tasks to the detriment of their subordinates, who came to absorb their activities.